Scheduling taxi services for a team of car relocators. (April 2021) - Morgenroth, Christopher; Boysen, Nils; Schwerdfeger, Stefan; Weidinger, Felix
Highlights: We investigate a novel routing problem. A team of drivers is taxied by a bus to efficiently move cars on board of a vessel. We derive efficient heuristic solution procedures. Managerial issues are investigated to speed up the process. Abstract: To transfer export cars on board of car carrier vessels in vehicle transshipment terminals or to rebalance the vehicles of car sharing providers in urban areas, plenty of car relocation moves need to be processed. Often in these settings, a team of drivers cooperates to execute a given set of car movements. They are chauffeured by a taxi towards their dedicated cars. Once dropped off, a relocator executes the relocation move, and returns to the central meeting point, where the next trip is started. This paper formulates the resulting routing problem, derives suited solution methods, and provides managerial insight.